A alternância causativo-ergativa no PB : restrições e propriedades semânticas - Larissa Santos Ciriaco (2007)
This dissertation aims to describe and explain the behavior of causative verbs in relation to the causative-ergative alternation in Brazilian Portuguese. The causative-ergative alternation consists in the appearance of the same verb in transitive sentences, like João quebrou o vaso and in intransitive sentences, like, o vaso quebrou. However, there are verbs that do not participate in this alternation, like o vento carregou as folhas / * as folhas carregaram. To pursue this question, the central hypothesis adopted here is that the semantic content of thematic relations is relevant to grammatical theory, as other authors (cf. cf. Whitaker-Franchi, 1989; Levin, 1993) also assume. We understandsemantics as an independent component of language, with its own properties and principles, and we search, within this component, the restrictions to the causativeergative alternation. In order to test this hypothesis, and adopting Cançados (2003, 2005) proposal for thematic roles, we analyzed 201 verbs of BP distributed in 527 sentences. Starting from Whitaker-Franchis proposal, we have reformulated her generalrestrictions to the phenomena. However, since those restrictions were not enough to explicate the verbs behavior, we proposed other lexical-semantic restrictions to the causative-ergative alternation with causative verbs, in general, and with psychological verbs, specifically, because of their atypical behavior. Therefore, this dissertation exposes the relevant semantic properties for the syntactic phenomena of the causativeergative alternation. We also propose a semantic analysis for the problem of transitivity, that is, an answer to the question of which form is the basic form of transitivity of a verb that appear as transitive and as intransitive.